ENTREPRENEURIAL ORIENTATION AND ITS EFFECT TOWARD SME PERFORMANCE THROUGH STRATEGIC FLEXIBILITY ON FASHION INDUSTRY IN MALANG - Kharisma, Pratasha Putra; Irawanto, Dodi W.; Rofiq, Ainur (Universitas Muhammadiyah Yogyakarta, 2020)
The relationship between strategy and performance is central to the study of strategic management. The main objective of this study is to examine the form of entrepreneurial orientation toward strategic flexibility and SMEs performance. By taking a more specific sample, this study uses SMEs in fashion in Malang as the object of research. Data was collected through questionnaires, with 31 owners of SMEs fashion in Malang being taken as respondents. The findings of the study revealed that only proactiveness had a significant direct effect on SMEs performance, while innovativeness, risk-taking, and proactiveness significantly influenced strategic flexibility. Proactiveness was found to have the greatest influence on strategic flexibility. This study shows the important role of strategic flexibility in strengthening the effect of entrepreneurial orientation on SMEs performance. Research implications and suggestions are discussed at the end of this article.